Coral Reef Management Information System : Integrated Data Management on Coral Reef Under Coremap - _, Giyanto; Swasti, Priti; Hakim, Dodi Amar (Journal of Indonesian Coral Reefs, 2011)
Coral Reef Information and Training Center (CRITC) is one of Coral reef Rehabilitation and Management Program (COREMAP) units which serve on coral reef of areas under the Research Center for Oceanography â Indonesian Institute of Sciences. Data Suplplied to the CRITC are collected from baseline studies and regular monitoring. At the second phase of COREMAP, CRITC are collected from baseline studies and regular monitoring. At the second phase of COREMAP, CRITC has conducted data grouping and processing for three major components: reef-helath, community-based fisheries monitoring (creel), social-economy plus spatial data. However managing these data was difiult due to former to way of data management: manual, scattered, non-centralized and non-standardized. It was then ebident an intergrated information system is needed to reduce data redudancy, allow easy data accessing and linking. In addition the new system should minimize changes to existing system. This way, data collection process is unaffected but a the same time system functionality is enhaced. To achieve the above objectives, CRITC has developed Coral reef Management Information System (CRMIS). CRMIS provides an intergrated , practical, easy-to-use online information system that support coral reef data management. CRMIS itself is a web 2 based application, bilingual (Indonesian and English), Support Web GIS (Geographical Information System), ad-hoc query (user-created search), time-series analysis and report. Web GIS faciltates online interactive thematic maps portraying reef health condition which is linked with other non spatial data (percentage of coral cover, cacth per unit effort or cpue and net-income of COREMAP locations). Hence CRMIS enabled stakeholders to easily get customized information for better reporting, research,planning and decision making.